P-Cresyl Sulfate Is a Valuable Predictor of Clinical Outcomes in Pre-ESRD Patients. (28th January 2014) - Lin, Cheng-Jui; Pan, Chi-Feng; Chuang, Chih-Kuang; Sun, Fang-Ju; Wang, Duen-Jen; Chen, Han-Hsiang; Liu, Hsuan-Liang; Wu, Chih-Jen
Abstract : Background/Aims . Previous studies have reported p-cresyl sulfate (PCS) was related to endothelial dysfunction and adverse clinical effect. We investigate the adverse effects of PCS on clinical outcomes in a chronic kidney disease (CKD) cohort study. Methods . 72 predialysis patients were enrolled from a single medical center. Serum biochemistry data and PCS were measured. The clinical outcomes including cardiovascular event, all-cause mortality, and dialysis event were recorded during a 3-year follow-up. Results . After adjusting other independent variables, multivariate Cox regression analysis showed age (HR: 1.12, P = 0.01 ), cardiovascular disease history (HR: 6.28, P = 0.0 2 ), and PCS (HR: 1.12, P = 0.0 2 ) were independently associated with cardiovascular event; age (HR: 0.91, P < 0.01 ), serum albumin (HR: 0.03, P < 0.01 ), and PCS level (HR: 1.17, P < 0.01 ) reached significant correlation with dialysis event. Kaplan-Meier analysis revealed that patients with higher serum p-cresyl sulfate (>6 mg/L) were significantly associated with cardiovascular and dialysis event (log rank P = 0.0 3, log rank P < 0.01, resp.). Conclusion . Our study shows serum PCS could be a valuable marker in predicting cardiovascular event and renal function progression in CKD patients without dialysis.